Investigation on the explosion limits and flame propagation characteristics of premixed methanol-gasoline blends. (August 2021) - Sun, Yanlong; Qian, Xinming; Yuan, Mengqi; Zhang, Qi; Li, Ziyuan
Abstract: Methanol-gasoline has the risk of combustion and explosion in the process of production, storage, transportation, and use, however, there are relatively few studies on its combustion and explosion characteristics. In this paper, the explosion limit of methanol-gasoline, the influence of temperature on its explosion limit, and the flame propagation characteristics of methanol-gasoline in a spherical glass container were studied by experimental means. It was known from the experiment that the lower explosion limit of methanol-gasoline increased with the increase of methanol volume fraction. The initial temperature had little effect on the explosion limit of M15 methanol-gasoline. With the increase of temperature from 25 to 100 °C, the lower explosion limit of M15 dropped by 2.784%, and the upper explosion limit of M15 ranged from 11.253% to 11.451% at the initial temperature of 40–120 °C. In the upward and downward propagation phases, the average propagation velocity of the flame in the spherical glass container was close to each other, about 0.31 m/s. The research outcomes of this study have important guiding significance for evaluating the explosion hazard characteristics of methanol-gasoline and supplementing and improving the technical indicators of methanol-gasoline.